Efeito da suplementação de polissacarídeos provenientes da Hancornia Speciosa (Mangaba) em camundongos com constipação e seu potencial biotecnológico - VITORIA HELENA DE OLIVEIRA TEIXEIRA REIS (2022)
Constipation is one of the most prevalent intestinal disorders and is characterized by the presence of hard and dry stools, excessive effort, infrequent bowel movements, abdominal distension and pain, and others. Dietary fiber intake is the major nutritional intervention recommended to treat this condition. Previous studies have investigated Hancornia speciosa laxative effect. So, this study aims to characterize the polysaccharides extracted from H. speciosa fruit pulp and evaluate the laxative effect of both soluble and insoluble isolated fractions on experimental model of chronic constipation. Monosaccharide composition of polysaccharides fractions were determined. For the experimental design, constipation was induced by loperamide administration, and mice were split in five groups (n=10): control (CT), constipation model (M), positive control (PSY), soluble polysaccharides fraction (SPS) and insoluble polysaccharide fraction (IPS). Food and water intake, weight gain, stool parameters, small intestine transit, cecal pH, and histopathological analysis of the large intestine were evaluated. Arabinose was the main neutral sugar presented on polysaccharides composition and the insoluble fraction showed to be effective on improving fecal parameters and alleviating constipation symptoms.